Protection against tuberculosis achieved by dissolving microneedle patches loaded with live Mycobacterium paragordonae in a BCG prime-boost strategy - Lee, Mi-Hyun; Seo, Hyejun; Lee, Moon-Su; Kim, Byoung Jun; Kim, Hye Lin; Lee, Du Hyung; Oh, Jaehun; Shin, Ju Yeop; Jin, Ju Young; Jeong, Do Hyeon; Kim, Bum-Joon (Frontiers in Immunology, 2023)
Introduction Skin vaccination using dissolving microneedle patch (MNP) technology for transdermal delivery is a promising vaccine delivery strategy to overcome the limitations of the existing vaccine administration strategies using syringes. To improve the traditional microneedle mold fabrication technique, we introduced droplet extension (DEN) to reduce drug loss. Tuberculosis remains a major public health problem worldwide, and BCG revaccination had failed to increase the protective efficacy against tuberculosis. We developed an MNP with live Mycobacterium paragordonae (Mpg) (Mpg-MNP) as a candidate tuberculosis booster vaccine in a heterologous prime-boost strategy to increase the BCG vaccine efficacy. Materials and Methods The MNPs were fabricated by the DEN method on a polyvinyl alcohol mask film and hydrocolloid-adhesive sheet with microneedles composed of a mixture of mycobacteria and hyaluronic acid. We assessed the transdermal delivery efficiency by comparing the activation of the dermal immune system with that of subcutaneous injection. A BCG prime Mpg-MNP boost regimen was administered to a mouse model to evaluate the protective efficacy against M. tuberculosis. Results We demonstrated the successful transdermal delivery achieved by Mpg-MNP compared with that observed with BCG-MNP or subcutaneous vaccination via an increased abundance of MHCII-expressing Langerin+ cells within the dermis that could migrate into draining lymph nodes to induce T-cell activation. In a BCG prime-boost regimen, Mpg-MNP was more protective than BCG-only immunization or BCG-MNP boost, resulting in a lower bacterial burden in the lungs of mice infected with virulent M. tuberculosis. Mpg-MNP-boosted mice showed higher serum levels of IgG than BCG-MNP-boosted mice. Furthermore, Ag85B-specific T-cells were activated after BCG priming and Mpg-MNP boost, indicating increased production of Th1-related cytokines in response to M. tuberculosis challenge, which is correlated with enhanced protective efficacy. Discussion The MNP fabricated by the DEN method maintained the viability of Mpg and achieved effective release in the dermis. Our data demonstrate a potential application of Mpg-MNP as a booster vaccine to enhance the efficacy of BCG vaccination against M. tuberculosis. This study produced the first MNP loaded with nontuberculous mycobacteria (NTM) to be used as a heterologous booster vaccine with verified protective efficacy against M. tuberculosis.